The complete mitochondrial genome of the common vole, Microtus arvalis (Rodentia: Arvicolinae) - Folkertsma, Remco; Westbury, Michael (Dr.); Eccard, Jana (Prof. Dr.); Hofreiter, Michael (Prof.) (2018)
The common vole, Microtus arvalis belongs to the genus Microtus in the subfamily Arvicolinae. In this study, the complete mitochondrial genome of M. arvalis was recovered using shotgun sequencing and an iterative mapping approach using three related species. Phylogenetic analyses using the sequence of 21 arvicoline species place the common vole as a sister species to the East European vole (Microtus levis), but as opposed to previous results we find no support for the recognition of the genus Neodon within the subfamily Arvicolinae, as this is, as well as the genus Lasiopodomys, found within the Microtus genus.